The impact of radiotherapy costs on clinical outcomes in breast cancer. Issue 2 (November 2015) - Boero, Isabel J.; Paravati, Anthony J.; Triplett, Daniel P.; Hwang, Lindsay; Matsuno, Rayna K.; Mell, Loren K.; Murphy, James D.
Abstract: Background and purpose: In cost-effective healthcare systems, the cost of services should parallel patient complexity or quality of care. The purpose of this study was to determine whether the cost of radiotherapy correlates with patient-related outcomes among a large cohort of breast cancer patients treated with adjuvant breast radiation. Materials and methods: 23, 127 women with non-metastatic breast cancer undergoing radiotherapy after breast conservation surgery were identified from the Surveillance, Epidemiology, and End Results database from 2000 to 2009. Medicare reimbursements were used as a proxy for cost of radiotherapy, and Medicare claims were examined to identify local toxicities, and breast cancer-related endpoints. The impact of cost on these outcomes was studied with multivariable Fine-Gray models to account for competing risks. Results: The median cost (and interquartile range) of a course of breast radiation was $8100 ($6700–9700). Increased radiation costs were not associated with the occurrence of treatment-related toxicities (all p -values > 0.05), ipsilateral breast recurrence ( p  = 0.55), or breast cancer-related mortality ( p  = 0.55). Conclusion: Higher costs for adjuvant radiation in breast cancer were not associated with a decreased risk of patient-related outcomes suggesting inefficiency in Medicare reimbursements. Future efforts should focus on prospective evaluation of alternative payment models for radiotherapy.